A case series of Kaposi's varicelliform eruption in dermatology in-patients in a tertiary care centre - Amiya Kumar Nath; Tukaram Sori; Devinder Mohan Thappa (Wolters Kluwer Medknow Publications, 2011)
Background: Recently, we noted increasing number of cases of Kaposi's varicelliform eruption (KVE) among dermatology in-patients who were being treated for various dermatoses, some of which have not been reported earlier to be associated with KVE, and hence, this report. Aims: This study was designed to identify various dermatoses in which KVE occurred, to study the clinical features, course and response to specific antiviral treatment, to establish the risk factors, and course of the primary dermatoses during the episode of KVE. Materials and Methods: We analyzed our data of dermatology in-patients in a tertiary care centre in South India from April 2008 to November 2009 (20 months). The data were tabulated and analyzed. Results: Twenty cases (12 female and 8 male patients) of KVE were seen. The mean age of the patients was 46.4 years. There were seven cases of erythroderma, four of pemphigus vulgaris, three of toxic epidermal necrolysis, two of airborne contact dermatitis (ABCD), one each of lichenoid drug rash, and drug rash with eosinophilia and systemic symptoms (DRESS). Underlying dermatoses for erythroderma were: ABCD (3), psoriasis (3), and cutaneous T-cell lymphoma (1). Possible source of infection could be identified in five cases: exogenous sources in four cases and endogenous source in one case. The mean incubation period for cases with known source was 5 days (range, 2-9 days). Eighteen patients responded favorably to acyclovir. None of our patients had recurrent KVE during the study period. Conclusion: KVE may complicate any dermatosis where the integrity of the skin is compromised. Diagnosis and early treatment are important and possible in most cases if suspected.